Finite size effects in perturbed boundary conformal field theories - Dorey, P.; Pillin, M.; Pocklington, A. [UNESP]; Runkel, I.; Tateo, R.; Watts, G. M.T. (Sissa Medialab Srl, 2000)
We discuss the finite-size properties of a simple integrable quantum field theory in 1+1 dimensions with non-trivial boundary conditions. Novel off-critical identities between cylinder partition functions of models with differing boundary conditions are derived.